1988
DOI: 10.1084/jem.167.3.777
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin receptors of phagocytes. Characterization of the Arg-Gly-Asp binding proteins of human monocytes and polymorphonuclear leukocytes.

Abstract: We have defined the cell surface molecules of human monocytes and PMN that bind to the chymotryptic cell binding domain of Fn and to a synthetic peptide, KYAVTGRGDS, based on the sequence of Fn, by affinity chromatography. Monocytes express two receptors that differ in their affinity for CBD-Sepharose and peptide-Sepharose, but that both recognize the RGD sequence. Only a single receptor is purified from PMN, which resembles the monocyte surface molecule that binds to peptide-Sepharose. These receptors are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
1

Year Published

1989
1989
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(73 citation statements)
references
References 39 publications
0
72
1
Order By: Relevance
“…Receptor expression on macrophages and K562 cells was analyzed by fluorescent flow cytometry as described (13,43).…”
Section: Facs Analysis Of Receptor Expressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Receptor expression on macrophages and K562 cells was analyzed by fluorescent flow cytometry as described (13,43).…”
Section: Facs Analysis Of Receptor Expressionmentioning
confidence: 99%
“…In addition, macrophage adhesion to fibronectin-coated surfaces affects a variety of macrophage functions including chemotaxis (25, 50), differentiation (8), secretion (7,45), and phagocytosis via immunologic receptors (12,52,66). Nonetheless, the moleculax nature of the interactions leading to these critical macrophage functions is unknown.Studies which have examined fibronectin receptors on macrophages in detail have demonstrated an unexpectedly large number of integrin and non-integrin fibronectin-binding proteins (10,13,16,17,29,42,59,63). Four integrin receptors with fibronectin binding capability have been identified on mononuclear phagocytes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, the findings indicate that the novel fibronectin fragments with opsonic activity for particulate activators are generated by cleavage from the amino-terminus. As with the gelatin binding plasma-derived fragment, 180K-opFnf (12), the synovial fluid fibronectin fragments with the BD4 epitope were opsonic via binding to the target particles (Figure 7), to provide a link to the fibronectin receptors on monocytes (12, [21][22][23]. The opsonic domain is the functional determinant that permits 180K-opFnf to distinguish asialylated microbial and sialic acid-deficient erythroid particulate activators (E') from fully sialylated nonactivators such as Es (24), and then provides the domain for interaction with the monocyte (12).…”
Section: Discussionmentioning
confidence: 99%